Double metal cyanides as efficient solid acid catalysts for synthesis of beta-amino alcohols under solvent-free conditions - Saikia, Lakshi; Satyarthi, J. K.; Gonnade, Rajesh G.; Srinivas, Darbha; Ratnasamy, P. (Catalysis Letters, 2008)
A novel application of Fe-Zn double metal cyanide complexes as solid, acid catalysts for regioselective synthesis of beta-amino alcohols under solvent-free conditions via ring-opening of epoxides with amines is reported for the first time. The conversion of epoxides to beta-amino alcohols is nearly 100%. In the reaction with styrene oxide, regioselective beta-amino alcohol formation is higher with aromatic than with aliphatic amines. Strong Lewis acidic Zn(2+) ions in the catalyst are probably the active sites in this reaction.
Keywords: beta-Amino alcohols; double metal cyanide (DMC); regioselective ring-opening of epoxides; Single crystal x-ray structure; solid Lewis-acid catalyst

Direct synthesis of amides from amines using mesoporous Mn-SBA-12 and Mn-SBA-16 catalysts - Kumar, Anuj; Nepak, Devadutta; Srinivas, Darbha (Catalysis Communications, 2013)
Manganese incorporated SBA-12 and SBA-16 catalyze the tandem reaction of aliphatic primary amine, aerial oxygen and ammonia solution at moderate conditions producing amide in yields as high as 50 mol%. The Mn-SBA-12 and Mn-SBA-16 catalysts with Si/Mn output molar ratio in the range 230 to 748 were prepared by the direct hydrothermal synthesis method and characterized. Weak acidity and Mn in +3 oxidation state are the key factors enable the synthesis of product amide in high yields. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aerial oxidation; Amide synthesis; Benzyl amine; Manganese incorporated SBA-12 and SBA-16; Mesoporous Mn-silica catalyst